Exercise training to reduce cardiovascular risk in patients with metabolic syndrome and type 2 diabetes mellitus: How does it work?. (May 2019) - Kränkel, Nicolle; Bahls, Martin; Van Craenenbroeck, Emeline M.; Adams, Volker; Serratosa, Luis; Solberg, Erik Ekker; Hansen, Dominique; Dörr, Marcus; Kemps, Hareld
Metabolic syndrome (MetS) – a clustering of pathological conditions, including abdominal obesity, hypertension, dyslipidemia and hyperglycaemia – is closely associated with the development of type 2 diabetes mellitus (T2DM) and a high risk of cardiovascular disease. A combination of multigenetic predisposition and lifestyle choices accounts for the varying inter-individual risk to develop MetS and T2DM, as well as for the individual amount of the increase in cardiovascular risk in those patients. A physically active lifestyle can offset about half of the genetically mediated cardiovascular risk. Yet, the extent to which standardized exercise programmes can reduce cardiovascular risk differs between patients. Exercise parameters, such as frequency, intensity, type and duration or number of repetitions, differentially target metabolic function, vascular health and physical fitness. In addition, exercise-induced molecular mechanisms are modulated by other patient-specific variables, such as age, diet and medication. This review discusses the molecular and cellular mechanisms underlying the effects of exercise training on cardiovascular risk specifically in patients with MetS and T2DM.